ANXIETY CAUSES AND FORMS IN OSAMU DAZAI’S NOVEL NO LONGER HUMAN - Cherilla, Ladya; Ekalestari, Susi (Universitas Islam Sumatera Utara, 2024)
This study analyses the various manifestations and determinants of the protagonist's anxiety. Anxiety, characterized by physiological responses such as increased heart rate, sweating, and breathing difficulties akin to fear, often arises spontaneously from unpredictable sources, distinct from the immediate nature of fears triggered by specific events. Within the spectrum of anxiety, there exists both typical apprehension and anxiety disorders, the latter representing a psychological condition stemming from uncontrolled fears that significantly disrupt an individual's life. To elucidate the protagonist's experiences, the researchers draw upon Freud's psychoanalytic theory and Savitri Ramaiah's insights into anxiety. Employing a qualitative descriptive design complemented by an analytical descriptive approach, the study addresses social issues and behaviors common across societies. The findings unveil three distinct forms of anxiety experienced by the protagonist: reality or objective anxiety, neurotic anxiety, and moral anxiety. Moreover, the research identifies environmental triggers, repressed emotions, and physical factors as key contributors to the protagonist's anxiety.